Influence Of E-WOM On Emotional Purchase Decisions in Ceviche, Fish, and Seafood Restaurants In Chimbote, Perú - Rodríguez, Ronald Floriano; Montano, Julio; Horna, Richard Fermín Contreras; Robles, Italo Sotero Capa; Yquiapaza, Freddy Bendezu (Journal of Ecohumanism, 2024)
The study investigates the influence of electronic word of mouth (e-WOM) on the emotional purchase decisions of consumers in ceviche, fish, and seafood restaurants in Chimbote, Peru. A mixed methodology was employed, combining the collection of quantitative data from 323 surveyed consumers and qualitative data obtained from 30 interviews, aiming to explore how e-WOM affects emotional purchase perceptions and choices in this specific context. The findings reveal a significant correlation between e-WOM and emotional purchase decisions, supported by a Rho value of 0.827 and a regression model that explains 73.9% of the variability in these decisions. Additionally, factors such as convenience, product accessibility, economic factors, and visual stimuli were identified as crucial influences on purchase decisions. In summary, this study contributes not only to the theoretical understanding of e-WOM and consumer behaviour but also offers practical implications for marketing strategies and experience management in this sector